Micro-dynamics mechanism of the phase transition behavior of poly(N-isopropylacrylamide-co-2-hydroxyethyl methacrylate) hydrogels revealed by two-dimensional correlation spectroscopy. Issue 5 (23rd December 2016) - Su, Gehong; Zhou, Tao; Liu, Xifei; Ma, Yanan
Abstract : The micro-dynamics mechanism of the volume phase transition of PNIPAM- co -HEMA hydrogels was established using temperature-dependent FTIR spectroscopy, PCMW2D, and 2DCOS analysis. Abstract : In this study, the micro-dynamics mechanism of the volume phase transition behavior of the poly( N -isopropylacrylamide- co -2-hydroxyethyl methacrylate) (PNIPAM- co -HEMA) hydrogel was investigated by temperature-dependent FTIR spectroscopy in combination with the perturbation correlation moving window (PCMW2D) technique and generalized two-dimensional correlation analysis. In conventional 1D FTIR spectra analysis, Boltzmann fitting curves showed that the volume phase transition temperature and the phase transition degree of the PNIPAM- co -HEMA hydrogel were lower than those of the pure PNIPAM hydrogel. They also showed that the PHEMA segments exhibit a similar "phase transition" behavior to the PNIPAM segments, which can be ascribed to the driving effect of the phase transition of PNIPAM segments. Furthermore, we found that the rate at which water molecules were expelled out of the gel structure during phase transition changed in an anti-S shape. PCMW2D spectra revealed that the phase transition can be divided into two processes (named I and II) upon heating, and further determined the temperature regions of processes I and II to be 21.8–31.4 °C and 31.4–36.5 °C, respectively. Finally, generalized 2D correlation analysis found that both processes I and II can be further divided into nine steps. From the deduced nine steps of process I, the significant role of PHEMA in the phase transition of PNIPAM segments was revealed. As for the deduced nine steps of process II, the driving effect of the phase transition of PNIPAM segments for PHEMA segments was confirmed.